Subordinación locativa y modal en tehuelche o aonek’o ?a?jen. Aspectos sincrónicos y diacrónicos - Fernández Garay, Ana (2017)
This article analyzes locative and manner clauses of the Tehuelche or Aonek’o ?a?jen, an indigenous language of the Argentinian Patagonia, spoken between the Santa Cruz river and the Strait of Magellan. At present, this language is facing an advanced process of extinction, despite Tehuelche community efforts to revitalize it. Locative and manner clauses are described according to a functional-typological frame, by taking into account the element that introduces them, their location in the sentence and the mood of the predicative core. In addition, the similarities found between both clauses are considered. Finally, the origin of the subordinators are explained by comparing them with those found in Selknam, a language that, like Tehuelche, belongs to the Chon family.